Skilled Labor Risk and Corporate Policies - Qiu, Yue; Wang, Tracy Yue (The Review of Corporate Finance Studies, 2021)
Abstract We measure U.S. listed companies’ skilled labor risk—that is, the potential failure in attracting and retaining skilled labor, by the intensity of discussions on this issue in 10-K filings. We show that this measure effectively captures firm risk due to the mobility of skilled labor. We find that an increase from the 25th to the 75th percentile in the skilled labor risk would increase the skilled labor wage by 22% (or $15,593) and also lead to higher equity-based incentive pay. The skilled labor risk also interacts with other corporate policies such as financial leverage, cash holdings, and M&As. (JEL G30, G32, G34, H20, J20, J24, J40, J41) Received September 28, 2020; editorial decision March 12, 2021 by Editor Andrew Ellul.